THE EXPRESSIVE SIDE OF UZBEK LANGUAGE AND THE FORMATION OF GRADUAL REALITION IN IT (Conferencea, 2023)
This article provides a scientific analysis of the expressive side of the language and the expression of gradual processes in it.